Application of Manure and Eco-Enzymes on Eucalyptus in Clay Mines at PT. Solusi Bangun Indonesia - Istikorini, Yunik; Mansur, Irdika; Padilah, Sinta Nur (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Open-pit clay mining has the potential to disrupt the environmental ecosystem. Reclamation is carried out to aid in the recovery of areas disturbed by mining processes. This study aims to determine the effect of applying manure and eco-enzymes on the growth of eucalyptus in post-mining clay land and to identify the optimal combination dosage of manure and eco-enzymes to enhance eucalyptus growth in these reclaimed areas. This study used Randomized Block Design with two factors: manure (0, 1, 1,5 kg) and eco-enzymes (0, 100, 150 ml). The results show that the interaction between manure and eco-enzymes had a significant effect on plant height and canopy thickness, although both treatments did not significantly affect plant diameter and canopy diameter. The best dosage for improving eucalyptus growth in post-mining clay land was 150 ml of eco-enzymes. Keywords: clay mining, eco-enzymes, eucalyptus, manure, reclamation